On equiasymptotic stability of solutions of doubly-periodic impulsive systems - Ignat'ev, A. O. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
A system of ordinary differential equations with impulse effects at fixed moments of time is considered. This system admits the zero solution. Sufficient conditions of the equiasymptotic stability of the zero solution are obtained.